Mutations in the Genes Regulating Methylene Tetrahydrofolate Reductase (MTHFR C→T677) and Cystathione β-Synthase (CBS G→A919, CBS T→c833) Are Not Associated with Myocardial Infarction in African Americans - Dilley, Anne; Hooper, W.Craig; El-Jamil, Muhydine; Renshaw, Mary; Wenger, Nanette Kass; Evatt, Bruce L (Thrombosis research, 2001)
Moderate hyperhomocysteinemia is a putative risk factor for cardiovascular disease. Molecular studies have demonstrated increased plasma homocysteine levels in the presence of DNA mutations in either the methylenetetrahydrofolate reductase (MTHFR) enzyme found in the remethylation pathway or the enzyme cystathione β-synthase (CBS) of the transsulfuration pathway. To determine whether the mutation C→T677 in the MTHFR gene or the T→C833/844ins68 and G→A919 mutations in the CBS gene are associated with myocardial infarction (MI) in African Americans, DNA was analyzed from samples obtained from a case–control study conducted at a large, inner-city hospital. One-hundred ten African American subjects with a diagnosis of MI and 185 race- and age-matched controls were recruited. Our results demonstrated that 15% of the MI cases were heterozygous for the C→T677 (MTHFR) mutation, while 1.8% were homozygous. When compared to the controls in which 15% were heterozygous and 2.1% were homozygous, no significant association with MI was observed. In addition, 34% of the cases were heterozygous for the T→C833 (CBS) mutation while 6% were homozygous. This is compared to 32% and 5% of the controls having the heterozygous and homozygous genotype, respectively. No significant association was observed for the T→C833 (CBS) mutation among the cases and controls. Although this mutation has no significant association with MI, the prevalence of the heterozygous state was higher than what has been reported for whites (12%). No mutations for G→A919 (CBS) were detected in the cases or controls. The racial differences of the CBS T→C833 polymorphism suggest that further investigation into the other areas of the CBS gene is needed.